Glucagon-like peptide 2 (GLP-2) accelerates the growth of colonic neoplasms in mice. Issue 8 (9th July 2004) - Thulesen, J; Hartmann, B; Hare, K J; Kissow, H; Ørskov, C; Holst, J J; Poulsen, S S
Abstract : Background: Glucagon-like peptide 2 (GLP-2) is an intestinotrophic mediator with therapeutic potential in conditions with compromised intestinal capacity. However, growth stimulation of the intestinal system may accelerate the growth of existing neoplasms in the intestine. Aims: In the present study, the effects of GLP-2 treatment on the growth of chemically induced colonic neoplasms were investigated. Methods: In 210 female C57bl mice, colonic tumours were initially induced with the methylating carcinogen 1, 2-dimethylhydrazine (DMH) and mice were then treated with GLP-2. Two months after discontinuation of the carcinogen treatment, 135 of the mice were allocated to one of six groups which were treated twice daily with 25 μg GLP-2, 25 μg Gly2-GLP-2 (stable analogue), or phosphate buffered saline for a short (10 days) or long (one month) period. The remaining 75 mice had a treatment free period of three months and were then allocated to groups subjected to long term treatment, as above. Results: Colonic polyps developed in 100% of the mice, regardless of treatment. Survival data revealed no statistical significant differences among the different groups but histopathological analysis demonstrated a clear and significant increase in tumour load of mice treated with Gly2-GLP-2. The tumour promoting effect of native GLP-2 was less pronounced but the number of small sized polyps increased following long term treatment. Conclusions: The present results clearly indicate that GLP-2 promotes the growth of mucosal neoplasms. Our findings highlight the need for future investigations on the effects of GLP-2 in conditions needing long time treatment or with increased gastrointestinal cancer susceptibility.